2004
DOI: 10.1300/j073v16n01_04
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Cultural Study of College Students' Travel Preferences

Abstract: To understand the behavior of tourists from different cultures, a cross-cultural study was conducted to examine Japanese and American college students' travel preferences. A psychographic approach based on value orientations was used to understand the relationship between travel preferences and students' cultural tendencies of horizontal and vertical individualism and collectivism. The study confirmed previous findings that Japanese and American college students have different cultural tendencies and travel pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…With respect to the tourism industry, numerous studies take as reference the country dimension to explain different aspects of tourist consumer behaviour: information search behaviour Gursoy & Umbreit, 2004), hospitality (McCleary, Choi, & Weber, 1998;Mok & Armstrong, 1998;Yuksel et al, 2006), destinations (Iverson, 1997;Kozak, 2002;Lee & Lee, 2009;Sakakida, Cole, & Card, 2004;You, O'Leary, Morrison, & Hong, 2000) and airline passengers (Kim & Prideaux, 2003). But although the presence of cultural differences and their impact has been dealt with in many aspects of human behaviour, very few studies analyse tourists' perceptions and their attitude and behaviour towards an urban destination in terms of their country of residence.…”
Section: [Table 1]mentioning
confidence: 99%
“…With respect to the tourism industry, numerous studies take as reference the country dimension to explain different aspects of tourist consumer behaviour: information search behaviour Gursoy & Umbreit, 2004), hospitality (McCleary, Choi, & Weber, 1998;Mok & Armstrong, 1998;Yuksel et al, 2006), destinations (Iverson, 1997;Kozak, 2002;Lee & Lee, 2009;Sakakida, Cole, & Card, 2004;You, O'Leary, Morrison, & Hong, 2000) and airline passengers (Kim & Prideaux, 2003). But although the presence of cultural differences and their impact has been dealt with in many aspects of human behaviour, very few studies analyse tourists' perceptions and their attitude and behaviour towards an urban destination in terms of their country of residence.…”
Section: [Table 1]mentioning
confidence: 99%
“…This could be explained by the fact that there are few travel agents/tour operators which offer student travel products in China. In contrast in the UK, organisations such as the Student Travel Association offer a wide range of products from full package tours to fl ight-only offers and have travel agencies on university campuses to simplify travel purchasing further (Sakakida et al, 2004). This shows that in the UK, student travel is an established market which is well served by specialist travel agencies and tour operators, while in China, it is just an emerging market, which has not yet been fully exploited by the travel industry.…”
Section: Sources Of Informationmentioning
confidence: 99%
“…Much of this money remained with locally owned businesses and communities, thus contributing to poverty alleviation and sustainable economic development (Tjolle, 2011). A review of relevant literature revealed that international students have become important participants in the international tourism industry (Huang, 2006;Michael et al, 2003;Ryan & Zhang, 2007;Sakakida, Cole, & Card, 2004;Shoham, Schrage, & van Eeden, 2004;Son & Pearce, 2005). China has become one of the biggest contributors to international student numbers in Britain (Higher Education Statistics Agency [HESA], 2012).…”
Section: Introductionmentioning
confidence: 99%